PEMBUATAN DAN KAJIAN SIFAT-SIFAT FISIKOKIMIA, MEKANIKAL, DAN FUNGSIONAL EDIBLE FILM DARI KITOSAN UDANG WINDU (Universitas Negeri Semarang, 2016)
This research aims to develop bioplastic as primary packaging or edible film of chitosan biopolymer derived from tiger prawn shells (Penaeus monodon), and to perform physicochemical and mechanical characteristics. An evaluation of the physicochemical properties of plastic films made from chitosan, by modifying the order of the different treatment processes, namely: a) DPMA (deproteination, demineralization, deacetylation), b) DMKA (demineralization, decoloration, and deacetylation) has conducted. The results of scanning FT-IR of the product shows that chitosan has identical spectrum compare of standard compound. Chitosan product from tiger prawn shells was the used as raw material for the manufacture of bioplastics. Experiments variable on the manufacture of edible film is a study of the effect of the use of different plasticizers (glycerol and sorbitol) and carboxylmethylcelullose (CMC) additives to the physicochemical, mechanical characteristics, and edible film functional. The results showed that all the edible film produced has a clear coat with a thickness between 0.05 to 0.3 mm. Meanwhile, the film density is highest at the DPMA + chitosan edible film sorbitol + CMC with a value of 1.7300 g/cm3. The use of plasticizer sorbitol provides great tensile strength but not too elastic, compared to the glycerol, while an increase in the average CMC can increase tensile strength and %Elongation. The use of different plasticizers and additives CMC does not significantly affect its functional properties, where the value of WVTR (water vapor transmission rate) is relatively the same on both types of edible films, ranging from 3.2409 to 4.8858 g /hr.m2.